Effect of Acu-TENS therapy on Zhongwan (cv12) Acupoint in streptozotocin induced Diabetic Rats - SUBBULAKSHMI,; GIRIJA SIVAKUMAR,; SATHIYA NARAYANA MURTHY, (International Journal of Pharma and Bio Sciences, 2017)
Acupuncture, a traditional medicine has been now used throughout the World for the treatment of many diseases including diabetes. We attempted to study the hypoglycemic effect of Transcutaneous Electrical Nerve Stimulation at acupoint (Acu-TENS) therapy on Zhongwan (CV12) acupoint in streptozotocin-induced diabetic rat (45 mg/kg/body weight)blood glucose level and its effects was compared with conventional anti-diabetic drug (pioglitazone 7.5mg/kg/body weight). Diabetes was induced in male albino wistar rats by administration of single dose of Streptozotocin(45 mg/kg/body weight) and the Zhongwan acupoint was stimulated with Acu-TENS of low frequency (15HZ), high intensity and with the pulse width of 5 sec, for 5 minutes daily without anaesthesia for 60 days. The effect of Zhongwan acupoint was studied on body weight, food and water intake and blood glucose. The Zhongwan acupoint treated rats significantly decreased blood glucose level and also produced beneficial effect on body weight. Food and water intake was also significantly decreased in CV12 acupoint treated rats. The results suggested that stimulation of Zhongwan acupoint reduced the blood glucose level in diabetic rats. Zhongwan acupoint has effect on reducing the blood glucose level may be stimulation of Qi (energy flow) and utilisation of energy due to mild muscle twitching during stimulation.